Sewage Sludge Composting and Pharmaceuticals - Egge Haiba; Lembit Nei (European Scientific Journal, ESJ, 2017)
Drug residues end up in the environment when sewage sludge or its compost is used as a fertilizer and they cause adverse effects there. Both, the producers and consumers seem to believe that drug residues decompose during sewage sludge treatment or in soil and do not affect the environment or humans. The acceptable level of drugs in different compartments of the environment is still disputable.